2013
DOI: 10.5897/jnbh12.014
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and haematological studies on effects of lycopene in Wistar rats subjected to psychological stress

Abstract: This study investigated the effects of prior lycopene supplementation on behaviour and haematology of Wistar rats subjected to psychological stress. Four groups of Wistar rats, each comprising seven animals were investigated: unstressed (U-Control), unstressed + lycopene (U+Lyco), stressed (SControl) and stressed + lycopene (S+Lyco). Olive oil was given by oral gavage to each rat in the groups, either singly or mixed with 10 mg/kg lycopene daily for two weeks. S-Control and S+Lyco groups were subjected to psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This agrees with the reports of Mohammed et al [23] and Krishna et al [34] who demonstrated that blood glucose level was increased significantly after 72 hours of STZ injection to Wistarrats. Streptozotocin has been shown to induce diabetes which is similarto human hyperglycaemic non-ketotic diabetes mellitus in animal models.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This agrees with the reports of Mohammed et al [23] and Krishna et al [34] who demonstrated that blood glucose level was increased significantly after 72 hours of STZ injection to Wistarrats. Streptozotocin has been shown to induce diabetes which is similarto human hyperglycaemic non-ketotic diabetes mellitus in animal models.…”
Section: Discussionsupporting
confidence: 83%
“…It was reconstituted in olive oil (Goya en espana, S.A.U., Savilla, Spain) to appropriate working dosage as earlier described by Ogundejiet al [23] with modifications. All other chemicals andsolvents used were of analytical grade.…”
Section: Chemicals and Lycopenementioning
confidence: 99%
“…It is a measure of erythrocyte strength and its ability to withstand varying osmotic gradients and it has being reported to be increased during oxidative stress [58] [59]. The greater the erythrocyte osmotic fragility, the weaker the tensile strength of erythrocyte membrane [23]. Similarly, hyperglycaemia associated with diabetes has been shown to increase the erythrocyte osmotic fragility and membrane lipid peroxidation in human erythrocytes [60].…”
Section: Discussionmentioning
confidence: 99%
“…30 mg lycopene in a gelatinous capsule was reconstituted in olive oil to appropriate working doses as described by Ogundeji et al [23] with little modifications. All treatments were administered orally once daily for a period four (4) weeks.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation